2017
DOI: 10.1152/ajpendo.00196.2016
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous H2S regulates endoplasmic reticulum-mitochondria cross-talk to inhibit apoptotic pathways in STZ-induced type I diabetes

Abstract: The upregulation of reactive oxygen species (ROS) is a primary cause of cardiomyocyte apoptosis in diabetes cardiomyopathy (DCM). Mitofusin-2 (Mfn-2) is a key protein that bridges the mitochondria and endoplasmic reticulum (ER). Hydrogen sulfide (HS)-mediated cardioprotection is related to antioxidant effects. The present study demonstrated that HS inhibited the interaction between the ER and mitochondrial apoptotic pathway. This study investigated cardiac function, ultrastructural changes in the ER and mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 39 publications
(37 reference statements)
0
48
0
Order By: Relevance
“…It is reported that DCM can cause the decrease expression of mitochondrial fusion protein and gap junction protein, 13, 14 although the mechanisms underlying these effects are not established. In addition, whether the activation of the gp78-ubiquitin proteasome system is involved in DCM is not clear.…”
mentioning
confidence: 99%
“…It is reported that DCM can cause the decrease expression of mitochondrial fusion protein and gap junction protein, 13, 14 although the mechanisms underlying these effects are not established. In addition, whether the activation of the gp78-ubiquitin proteasome system is involved in DCM is not clear.…”
mentioning
confidence: 99%
“…There is ample evidence that cardiovascular disease is related to decreased expression of CSE [46, 47]. Our previous studies have found that H 2 S regulates the interactions and cause a switch among cell death pathways during hyperglycaemia [25, 32]. In the present study, we established a classic type I diabetic rat model to investigate the protective effects of H 2 S against hyperglycaemia-induced cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have shown that mitochondria are involved in the process of high glucose injury through enhancing the production of mitochondrial ROS and opening of the mPT pore [25]. The formation of ROS from cardiomyocytes is a key factor in the pathogenesis of diabetic complications [43, 48, 49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings denoted degeneration of cardiac muscle fibers. In support, these changes were recently attributed to upregulation of reactive oxygen species (ROS) [30] . Furthermore, another group [31] added and confirmed by proving that using a potent antioxidant as tiron could interfere with ROS pathway and hence prevents apoptosis-related cardiovascular diseases including diabetic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 90%